Evaluasi Kurikulum Merdeka: Tantangan dan Solusi dalam Penerapannya - Harum Melati Suci; Lara Fultri; Merika Setiawatic; Hendri Budi Utama (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The implementation of the Merdeka Curriculum faces various challenges, such as teacher readiness, limited resources, and lack of stakeholder support. This study aims to evaluate the implementation of the Merdeka Curriculum by identifying key challenges and formulating strategic solutions. The method used is a literature review by analyzing academic journals and policy documents. Data were obtained from nationally and internationally indexed journals discussing the implementation of this curriculum. The results indicate that although the Merdeka Curriculum offers flexibility, challenges remain in teacher preparedness, school infrastructure, and suboptimal evaluation mechanisms. Variations in the use of technology and teaching methods, limited access in certain areas, and unclear evaluation systems are the main obstacles. Solutions that can be implemented include technology-based teacher training, increased access to educational resources, and a more adaptive evaluation system. Support from the government, society, and educational institutions is a key factor in the successful implementation of this curriculum.